Building Taxon Substitution Guidelines on a Biological Control Foundation. Issue 4 (25th April 2014) - Aslan, Clare E.; Aslan, Austin; Croll, Don; Tershy, Bernie; Zavaleta, Erika
Abstract When a species becomes extinct, its ecological functions are lost as well. Taxon substitution is a controversial approach to restoring such functions via introduction of non‐native species known to serve similar functions elsewhere. Due to the possibility of nontarget effects from such introductions, taxon substitution has been proposed and implemented in only a few systems, but these attempts have successfully restored functions. As a conservation tool, taxon substitution bears similarity to biological control, wherein species are also introduced for their ecological function with consideration of potential nontarget effects. To improve both the safety and efficacy of taxon substitution, regulatory bodies that currently issue guidelines for biological control can do the same for taxon substitution. Indeed, many biological control guidelines would apply well to taxon substitution. We examine the standard practices followed by biological control programs and propose corresponding taxon substitution guidelines. Integration of taxon substitution into the existing national and international environmental management conversation will improve the tool and has the potential to enhance conservation efforts across a wide diversity of systems if appropriate and stringent precautions are taken.